Virological outcomes of second-line antiretroviral therapy for HIV-1 patients in center of excellence, Gandhi Hospital, Secundrabad, Telangana - M. Raja Rao; Deepak Pandharpurkar; Krishna Gudikandula; Mallikarjun P. (International Journal of Medical Research and Review, 2019)
Introduction: In India, ART service was established in 2004 and viral load facility was started in 2009 through National Public Health Laboratory (NPHL). Phased scale-up has been planned to efficiently and successfully expand viral load testing services, taking into account the targets for enrollment of People Living with HIV in to Anti Retroviral Therapy program.Methods: This is an observational study conducted at the Centre of Excellence (COE), Gandhi Hospital Secundrabad. It is a referral centre for evaluation of patients suspected of treatment failure from ART centers. Data of all patients >18 years of age who were started on second line therapy due to failure of first line ART was taken in the study. The data of patients admitted between the time period of January 2009 to January 2010 was included.Results: A total of 147 HIV infected patients received second line ART of which 114 were men and 33 were women. Of these, 147 were treated with regimen TL, ATV/r. The most common cause to switch on second line ART was combined immunological and clinical failure (135) followed by all three failure (12).Mean baseline CD4 count was 220.06 (95% confidence interval [CI]: 243.73-196.38) and mean base line of PVL of patients was 291356.6 cells/mm3 (95% CI: 364843.8-217869.29) copies/ml, respectively.Conclusion: Good long term outcome as well as virological suppression in patients starting second line therapy under programmatic conditions in India. This early mortality can be circumvented by introducing routine virological monitoring in the program which will help in early detection of patients with failure.